Inner Experience and Illumination in Suhrawardi's Philosophical Thought - Siti Mursalina; Fetti Nur Fatimah; Ilham Mubarok; Dyah Qotrunnada (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2025)
Suhrawardi (1154-1191) is one of the leading philosophers in the Islamic philosophical tradition who introduced the Philosophy of Illumination (Hikmat al-Ishraq) as a synthesis between Peripatetic rationalism and mystical experience. Suhrawardi emphasized that enlightenment (isyraq) through intuitive experience has a fundamental role in understanding reality. The main concept in his philosophy is the hierarchy of light, where everything in existence is a graded manifestation of the Light above all light (Nur al-Anwar). This research uses the literature review method by examining texts. The results show that Suhrawardi's theory of illumination not only contributed to the development of Islamic philosophy, but also had an influence in mysticism and Sufism. By emphasizing the importance of inner experience and illumination in achieving the essence, Suhrawardi's thought remains relevant in the study of Islamic philosophy and contemporary epistemological discussions.